An introduction to Java programming : Developing applets using Microsoft Visual J++ - Stoker, Carol; Plew, G. Thomas (Cambridge, MA : Course Technology, 1998)
This book is about: Getting started with Microsoft Visual J++ and Java; Understanding and Using objects; Using variables and expressions; ...
Keywords: Java; Computer program language; Microsoft Visual J++.; Java (Computer program language); Microsoft Visual J++.